Anticipatory Postural Adjustments in Standing Reach Tasks Among Middle-Aged Adults With Diplegic Cerebral Palsy. Issue 4 (3rd July 2016) - Su, Ivan Y. W.; Chow, Daniel H. K.
ABSTRACT: Previous studies reported that children with cerebral palsy (CP) exhibited premature anticipatory postural adjustments (APAs) with high variability and excessive activity in the frontal plane. To better understand the effects of gross motor functioning level on APAs over the life course, the authors examined the presence and consistency of APAs in 11 adults with diplegia at 2 functioning levels against 8 age-matched healthy adults during unilateral and bilateral reaching. Results revealed an anticipatory vertical torque (TZ ) and an increased likelihood of APAs during bilateral reaching for the lower functioning group. It is postulated that APAs may first emerge in TZ in CP. Results also indicated an excessive premovement postural activity in the frontal plane in both CP groups.